Everyone is capable of leaving a legacy behind - Abdul Razak, Mohd Abbas (Kulliyyah of Islamic Revealed Knowledge & Human Sciences, IIUM, 2021)
A legacy is something noble, precious or even useful that we leave behind for others before we make an exit from this world. For the vast majority of us, the imagination that comes to our mind with regard to a legacy is that of a monumental structure, system, an ideology, statue of a most influential leader, etc. Some even think of a huge sum of money you leave behind for posterity. When such imaginations come to our mind, as laymen, we might feel that we have nothing great to contribute to others when we compare ourselves with those who are affluent or influential. Conversely, from the Islamic perspective, each and every one of us is capable of doing something trivial, yet it can be great in the sight of Allah and others when we are no longer there.